Effect of fungicide application on Wheat Head Blight, occurrence of Fusarium spp. and mycotoxin production. - Baturo-Cieśniewska, A.; Lukanowski, A.; Kolenda, M. (Plant Breeding and Seed Science, 2011)
The aim of the study was to determine if azoxystrobin and metconazole used for the control of wheat FHB at half, full, and quarter more the recommended dose rate may affect in differentiated way on the occurrence of Fusarium spp. and their ability to mycotoxin production in harvested grain, in wheat ears artificially inoculated with two DON-producing isolates of F. culmorum. Macroscopic evaluation showed high incidence of fusariosis. Plant health in the plots where the heads were artificially inoculated and fungicide was not applied was similar to the protected ones. Only increasing the dose metconazole resulted in a stronger reduction of fusariosis. The advantageous effect of azoxystrobin was not observed. Mycological analysis of harvested grain showed the presence of a number of F. culmorum, but from samples sprayed with metconazole it was isolated in smaller quantities. Also F. avenaceum, F. graminearum, F. poae and F. tricinctum were isolated. Molecular analysis showed the presence of F. culmorum in all samples of harvested grain. Also genes from Tri cluster were identified, involved in the synthesis of type-A and type-B trichothecenes - especially DON and 3Ac-DON. Chromatography revealed the presence of small quantities of mycotoxins. In all samples DON and 3Ac-DON were predominant. In general, F. culmorum isolate, which caused weaker symptoms of FHB and was less numerously isolated from grain that the other one, produced smaller amounts of mycotoxins. Samples protected with azoxystrobin contain the largest quantities of DON. Effect of different doses of fungicides on the number of mycotoxins was not clearly established...